Mechanical performance of fly ash geopolymeric mortars containing phase change materials - Kheradmand, Mohammad (2018)
European Union (EU) aims to achieve nearly zero-energy (public) building (NZEB)  by the end of 2018. This very ambitious target would be more easily fulfilled if high- thermal performance materials like phase change materials (PCMs) are to be used.  This paper reports experimental results on the mechanical properties of  geopolymeric mortars containing PCMs at ambient temperature and after exposure  to high temperature. The results show that the inclusion of PCMs is responsible for a  reduction of the mechanical strength of the mortars. Several mixtures showed an  increase in compressive strength after being exposed to high temperatures. Since  PCMs are made of flammable materials, geopolymeric mortars are more advantageous than Portland cement-based mortars for PCM incorporation.